The prevalence risk of anxiety and its associated factors among university students in Malaysia: a national cross sectional study - Mohamad, Nurul Elyani; Mohd Sidik, Sherina; Akhtari-Zavare, Mehrnoosh; Abdul Gani, Norsidawati (BioMed Central, 2021)
Background: Anxiety disorder is one of the most common mental health problems worldwide, including Malaysia, and this issue has gained concern and attention from many, including experts and authorities globally. While average levels of stress and worry may help to motivate students to perform well in their studies, excessive feelings will increase their level of anxiety. Methods: A cross-sectional study was conducted at selected government and private universities throughout Malaysia. A total of 1851 students participated in this study. The students were asked to complete self-administered questionnaires, including socio-demographic, academic, and psychosocial characteristics. The Generalized Anxiety Disorder-7 (GAD-7) questionnaire was used to measure the prevalence risk of anxiety among the students. Chisquare analysis was conducted to find the relationship between the variables and anxiety, and multivariate logistic regression analysis was used to identify the predictors. Results: The response rate was 97.90%, where 1821 out of 1860 students participated in the study. The prevalence risk of anxiety in this study was recorded at 29%. The data revealed that academic year, financial support for the study, alcohol consumption, poor sleep quality, body mass index (BMI), having a good friend in the university, having doubt regarding the future, actively involved in the society, and having problems with other students and lecturer(s) were significantly associated with risk of anxiety; with the academic year as the primary predictor. Conclusions: The findings highlight the current prevalence risk of anxiety among university students in Malaysia. The outcome of this study can serve as the evident baseline data and help with the development of specific interventions in addressing and managing the issue appropriately.